Cloud-to-ground lightning observations over the Western Antarctic region - Yusop, Norbayah; Zainudin, Siti Khalijah; Wan Mohd Nor, Wan Nur Arina; Alhasa, Kemal Maulana; Ahmad, Mohd Riduan; Mohammad Sabri, Muhammad Haziq; Abdullah, Mardina; Mohd Esa, Mona Riza; Suparta, Wayan; Gulisano, Adriana Maria; Cooray, Vernon (Elsevier B.V., 2019)
This paper presents the observations and characterization of Cloud-to-Ground (CG) lightning activity in Western Antarctica in a region that covers the Amundsen/Bellingshausen Sea (ABS), the Antarctic Peninsula (AP) and the Weddell Sea (WS). Lightning data have been collected by a lightning detector (Boltek LD-350) and an atmospheric electric field mill (EFM-100) sensors deployed at the Carlini Base on the Antarctic Peninsula (CARL: 62.23oS, 58.63oW). The flash rate and flash multiplicity were analysed for three different seasons within a 1,000 km range, starting at the end of summer (February 2017) and ending in winter (July 2017). Three storm days for each month (within the 1,000 km radius from the LD sensor) with three composite active thunderstorms (labelled as Storm region A, B, and C) for each day have been selected from a collection of storm days between February and July 2017. A total of 355,899 flashes have been recorded with 156,190 Positive CG and 199,709 Negative CG flashes from these 54 thunderstorms. In total, Positive CG flash counts made up around 43.9% of the total detected CG flashes. Most of the Positive CG flashes (>80%) had only 1 or 2 strokes with a maximum number of 5. For Negative CG flashes, the average multiplicity and the maximum multiple stroke were 1.2 and 16 respectively. Most CG flashes were detected during the summer and fall months. Positive CG flashes were prevalent in Western Antarctic storms even during the winter. The mean, median and range of the ratio of Positive CG to Negative CG flashes were 0.7, 0.718 and 0.217–1.279, respectively.